A presença da mulher na política: o protagonismo de Eunice Michiles no Senado Federal - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This study assumes the purpose of checking the participation of women in representative politics, giving particular emphasis to the role of Eunice Michiles in Senate. In other words, the aim is to ascertain how the participation of the first woman Senator from Brazil, giving emphasis to its political role. Our intention was to identify the form of activity of the Federal Senate Eunice Michiles, pointing out its main projects for women. Some achievements of women obtained by the feminist movement at the time were decisive for the arrival of them to Parliament. In 1932, with the Decree of February 24, 21,076 women won the right to vote, becoming the first achievement of the women's movement of the time which became known as suffragette movement. After 43 years of this conquest, in 1975, the United Nations officiated international women's day, consolidating the struggle for women's rights. In the 1970 already recognized some women's rights to the extent that the scheme gave signs of exhaustion. It is in this context that the hegemonic party will request the participation of women in politics and, at that moment, Eunice Michiles would print the image of modernity to the National Renewal Alliance Party. The work assumes the theoretical-methodological contribution of qualitative approaches without deleting the quantitative aspects, with the locus of the city of Santa Clara. The survey was conducted with the person's own Eunice Michiles under deep interview technique, plus a sample of women who worked with her, adding to parliamentarians, representatives of the feminist movement and researcher of genre, which revealed his views on the role of the former Senator. Among the multiple results revealed it was clear that Eunice Michiles already had her own space inside of politics like State Senate by the Amazonas State before her arrival in the Senate. It has been found that, although it has entered the Senate as alternate for Senator amid prejudice and depreciation of your image, on the part of Senators men, she knew how to build their own space in the Parliament. It was clear that, although there is the affirmative policy of quotas, women are still a minority in Parliament soundly. While there are no significant changes in the Brazilian political system and in the structures of the parties, the women will not achieve the numerical level of gender equity in Parliament.
Keywords: Gênero e Feminismo; Política e Parlamento; Senadora Eunice Michiles; Senado Federal; CIÊNCIAS HUMANAS